Picasso and the Theater: From Harlequin to Pegasus – The Modernist Fine Art and Theater Turn - Popović Bodroža, Ana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Following the method of interdisciplinary studies, this paper analyzes Pablo Picasso's relation to theater through his paintings, theater work, and the influence of theater not only on the themes of his paintings but also on the affirmation of the Avant-garde, the Cubist experiments and practices, the breakthrough of Cubist ideas across the medium of theater. The entire Picasso's art is presented in the light of several major artistic Avant-gardes of which he was the founder and ideologist (the “father” of Cubism, inventor of Collage, the first Ready-mades and Constructivist sculptures, initiator of so-called Primitive Art, early Surrealism, etc.). However, it seems that the most significant field of his work, the “Cubist Revolution”, has entered a new dimension through the presentation—performance—on the theater stage and in high culture circles. The influence of the stage and the early “Total Design” concept on his art and the perception of space/object within Cubism and beyond are exceptional, as is the performative act and the presentation of his ideas through the language of the stage. In this case, one medium, by its nature the more communicative one (theater), takes the role of presenting the other, more hermetic one (fine art). That influenced, in multiple ways, the affirmation and acceptance of Pablo Picasso's art. Starting with the early fascination with characters such as Harlequin, Pierrot, circus horse riders, dancers, and jugglers, present in his paintings (“Blue Phase” 1901–1904, “Pink Phase” 1905–1907, and beyond), this paper focuses on his collaboration with Serge Diaghilev and the “Russian Ballet” (“Ballets Russes”, 1917–1924), the elite troupe of Russian dancers who settled in Paris as the epicenter of modern art and started their productions there. Picasso was chosen to design the stage, the Cubist costumes, and the monumental theater curtains. Among other ballets, an outstanding piece, “Parade” by Erik Satie (1917), is seen today as a borderline performance, a turning point in ballet art, the start of its revolutionizing process towards contemporary ballet. By creating costumes resembling totems and the stage design based on Cubist division and perception of space, made from geometric shapes and particles (“facettes”), Picasso has taken the theater back to its primordial origins, its shamanic character. The paper elaborates on the relation of the ballet “Parade” with the ideas and theater theories of the theatrologist and sociologist Richard Schechner. Additionally, it addresses the question of a slow, postponed social reception and the (un)acceptance of Picasso's work and his comrades, a theme elaborated by the philosopher Jean-Francois Lyotard in the field of aesthetics and post-aesthetics.
Keywords: Picasso; Schechner; Harlequin; “Russian Ballet”; “Parade”